Stroke: costly public health problem - Pawłowski, Witold; Goniewicz, Krzysztof; Goniewicz, Mariusz; Lasota, Dorota (Journal of Education, Health and Sport, 2018)
An apoplectic stroke is one of the main causes of diseases and mortalities in the world. Mainly, it concerns elderly people, more often men than women. Worldwide it is the second biggest killer, third in developed countries, as a result of the cardiovascular system’s diseases.The research presents the general characteristics of brain stroke, characterized risk factors and complications of brain stroke, and principles of brain stroke treatment. The most common form of strokes are called ischemic stroke, brain infarction, around 85% of all strokes. The greater and the most important an apoplectic stroke’s factor is high blood pressure. It makes it four times more possible to be struck by an apoplectic stroke. An apoplectic stroke is an urgent state requiring conservative treatment and at times even surgical one. According to the European Stroke Initiative, proper patient care suffering from a quite recent stroke regarded as an urgent state depends on a 4-element chain: fast diagnosis and response to symptoms of a stroke, urgent informing emergency medicine service, urgent transport to a hospital (earlier information about its arrival), fast and proper diagnosis and hospital treatment.